2020
DOI: 10.1002/adsc.202000199
|View full text |Cite
|
Sign up to set email alerts
|

Selective C(sp3)−H Functionalization of Alkyl Esters with N‐/S‐/O‐Nucleophiles Using Perfluoroalkyl Iodide as Oxidant

Abstract: An efficient transition metal‐free approach to achieve the selective cleavage of the α‐carbonyl C(sp3)−H bond in alkyl esters by using inexpensive, low‐toxic, and insensitive perfluoroalkyl iodide as the radical initiator has been developed. A variety of enamides, N‐heterocycles, amides, thiophenols, and phenols could be successfully incorporated into functionalized alkyl groups by intermolecular amination, thioetherification, and etherification. The distinguishing features of this CDC reaction are its broad s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Additionally, Zhao et al. observed that, for the liquid phase hydrogenation of toluene over Pd/SiO 2 , a hydrophylic solvent adsorbed strongly on the support strongly limiting the hydrocarbon conversion [55] . Another study by Bertero et al.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Zhao et al. observed that, for the liquid phase hydrogenation of toluene over Pd/SiO 2 , a hydrophylic solvent adsorbed strongly on the support strongly limiting the hydrocarbon conversion [55] . Another study by Bertero et al.…”
Section: Resultsmentioning
confidence: 99%